Nanostructured tio2 and Pedot Electrodes with Photovoltaic Application - Gacitua-Santalices, M; Gacitua-Santalices, M (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In this work, nanostructured TiO2 and poly-3,4-ethylenedioxythiophene (PEDOT) layers were electrochemically prepared over transparent electrodes. Morphological characterization evidenced the presence of nanostructures as planed with 50-nm-wide TiO2 rod formations followed by 30-nm-wide PEDOT wires. Different characterizations were made to the deposits, establishing their composition and optic properties of the deposits. Finally, photovoltaic cells were prepared using this modified electrode, proving that the presence of PEDOT nanowires in the cell achieves almost double the efficiency of its bulk analogue. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.